Very High Cycle Fatigue (VHCF) of notched specimens: a review (Fracture and Structural Integrity, 2025)
A large number of mechanical components are subjected to fatigue loading beyond 106 cycles. The VHCF behaviour of smooth specimens has been extensively investigated in the recent years, even if more efforts are necessary to reveal the mecahnism governing failures. On the other hand, the influence of notches in the VHCF regime remains relatively unexplored. In the present review, the available studies on the VHCF behaviour of notched components have been analysed and compared.The review highlights that  multiple approaches for accounting for the stress concentration introduced by notches are available in the literature and that notches alter the failure mechanisms compared to smooth specimens. In general, a model for the design of complex structures against VHCF failures and with notches/geometric discontinuities is missing, and more experimental data for different materials are to be obtained to prove the validity of the approaches already available in the literature or employed for the High Cycle Fatigue (HCF) life range. Moreover, since the ultrasonic fatigue testing machines are mainly used for the tests, different definitions for the stress concentration factors have been found in the literature, since, with these types of tests, the stress distribution within the specimen depends on the wave propagation and on the resonance condition.
Keywords: Very High Cycle Fatigue; notch effect; ultrasonic fatigue testing